TOXICITY OF 2-METHOXYETHANOL ON BALB-C MOUSE SPERMATOGENESIS - Tania, Putu Oky Ari (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2013)
The research was designed to find out the toxicity of 2-methoxyethanol (2-ME) to the number of spermatogenic cells. Ten mice divided into 2 groups, control group was administered by 0.5 % CMC (negative control) and treatment group were administered by 2-ME dose 100 mg/kg body weight. Days thirteenth until sixty thirth, the mice were administered by aquabides orally, andat Â the end of the treatment, the mice were sacrified.Â  The number of spermatogenic cells were observated histologically with Hematoxylin-Eosin staining. The observation shows that 2-ME decreases the number of spermatogenic cells, especially spermatocyte I. Exposure of 2-ME destructs anatomy of tubulus seminiferusin testicular, which is affects degradation of ephitellium and atopy of testicular.